ANALISIS PSIKOLOGI PENDIDIKAN TERKAIT KESEIMBANGAN NILAI AKADEMIK DAN HAFALAN AL-QUR’AN PADA SISWA KELAS 6 UPTD SDN 4 MADDUKKELLENG - Nurrahmadhani Nadar; Andi Muhammad Darul Aqsah; Karina Arianti; Erfika; Rifki; Putri Amanda Lestari; Besse Mutmainnah; Indo Santalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the efforts to achieve balance between formal academic grades and the Al-Qur’an memorization target (tahfidz) among 6th-grade students at UPTD SDN 4 Maddukkelleng, who are in a dynamic cognitive development phase and face significant dual curriculum demands. The main challenges identified are the high cognitive load and psychological pressure (stress and achievement anxiety) stemming from both internal and external expectations. The students' success in balancing these two demands heavily relies on mastering time management (such as Time Blocking and Minimal Spacing strategies), adaptive learning strategies (Active Recall and Chunking), as well as self-discipline and mental resilience (grit). Furthermore, the central role of social support particularly from tahfidz teachers, assisting teachers, and parents is proven to be essential in fostering students' intrinsic motivation and self-efficacy, ensuring that the tahfidz process is based on awareness and love rather than coercion. This integrated approach ultimately aims to produce individuals who are not only academically and memorizationally successful, but also responsible, focused, and morally upright.